2018
DOI: 10.1186/s12890-018-0656-y
|View full text |Cite
|
Sign up to set email alerts
|

Mixed pneumonic plague and nosocomial MDR-bacterial infection of lung: a rare case report

Abstract: BackgroundPlague is a life-threatening disease caused by the bacterium, Yersinia pestis. Madagascar is the leading country for human plague cases worldwide. Human plague is a serious disease, particularly in its septicaemic and pneumonic forms. We report a case of pneumonic plague co-infected by a MDR-Stenotrophomonas maltophilia.Case presentationA 24 year-old man originated from Soavinandriana, a plague focus, felt uneasy and developed high fever with chills. He started treatment by himself, by private medica… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
5
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
6
1
1

Relationship

2
6

Authors

Journals

citations
Cited by 8 publications
(5 citation statements)
references
References 25 publications
0
5
0
Order By: Relevance
“…Relatively low specificity (59% overall, 44.7% for PP) of the F1RDT compared with that for culture might be caused by several factors, including badly preserved and contaminated field samples and long delays in transport to laboratory; both factors could lead to negative results from culture even if the cultured material originated from a true plague case. In addition, negative culture results might have resulted from administration of antimicrobial drugs by local health officials before sampling ( 17 ), whereas F1RDT results remained positive >3 weeks after treatment initiation ( 18 ). Moreover, pain, fever, and cough are often treated with self-medication in Madagascar ( 19 ).…”
Section: Discussionmentioning
confidence: 99%
“…Relatively low specificity (59% overall, 44.7% for PP) of the F1RDT compared with that for culture might be caused by several factors, including badly preserved and contaminated field samples and long delays in transport to laboratory; both factors could lead to negative results from culture even if the cultured material originated from a true plague case. In addition, negative culture results might have resulted from administration of antimicrobial drugs by local health officials before sampling ( 17 ), whereas F1RDT results remained positive >3 weeks after treatment initiation ( 18 ). Moreover, pain, fever, and cough are often treated with self-medication in Madagascar ( 19 ).…”
Section: Discussionmentioning
confidence: 99%
“…The imaging manifestations of plague are rarely reported and are not speci c. By reading a large number of literature, we summarized the following: 1) Pulmonary consolidation: Patchy, localized, or diffuse consolidation shadows appear in the lungs, with blurred edges that can merge into large areas, and may even show "white lung" changes [13]. The pathological basis of this change is diverse and may be pulmonary hemorrhage, pulmonary edema, or in ammatory exudation.…”
Section: Discussionmentioning
confidence: 99%
“…There are also additional descriptions of Y. pestis coinfection with nonstreptococcal pathogens. Case reports of multidrug-resistant Stenotrophomonas maltophilia and leptospirosis coinfection with plague have been previously published, and a genomic study of a sixth-century plague victim showed evidence of invasive Haemophilus influenzae (serotype b) (Andrianaivoarimanana et al, 2018 ; Bertherat et al, 2014 ; Guellil et al, 2022 ). However, based on the available case data, Y. pestis–Streptococcus coinfection appears to carry a greater risk of mortality than other pathogens in combination with Y. pestis .…”
Section: Discussionmentioning
confidence: 99%